2012
DOI: 10.1111/j.1360-0443.2012.03953.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of a novel cannabis use intervention delivered by telephone

Abstract: A brief course of motivational interviewing plus cognitive behavioural therapy delivered by telephone can help to reduce cannabis dependence and promote abstinence in the short term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
58
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 33 publications
0
58
1
Order By: Relevance
“…Other cannabis use outcomes in the same two studies reported insignificant results (Gates et al, 2012;Rooke et al, 2013). The effect of web or telephone interventions on severity of dependence was mixed, with one study showing a significant improvement (Gates et al, 2012) (Rooke et al, 2013). One study reported the effect on cannabis problems and reported a significant decrease (Gates et al, 2012).…”
Section: Telephone or Web-based Cbt Or Counselling Versus Wait-list Omentioning
confidence: 89%
See 4 more Smart Citations
“…Other cannabis use outcomes in the same two studies reported insignificant results (Gates et al, 2012;Rooke et al, 2013). The effect of web or telephone interventions on severity of dependence was mixed, with one study showing a significant improvement (Gates et al, 2012) (Rooke et al, 2013). One study reported the effect on cannabis problems and reported a significant decrease (Gates et al, 2012).…”
Section: Telephone or Web-based Cbt Or Counselling Versus Wait-list Omentioning
confidence: 89%
“…Three studies (Gates, Norberg, Copeland, & Digiusto, 2012;Rooke, Copeland, Norberg, Hine, & McCambridge, 2013;Tossmann, Jonas, Tensil, Lang, & Struber, 2011) compared telephone or web-based interventions versus wait-list or education controls. Interventions included telephone-CBT (Gates et al, 2012), web-CBT (Rooke et al, 2013) and web-counselling (Tossmann et al, 2011).…”
Section: Telephone or Web-based Cbt Or Counselling Versus Wait-list Omentioning
confidence: 99%
See 3 more Smart Citations